KEANEKARAGAMAN JENIS CAPUNG (ODONATA) PADA RUANG TERBUKA HIJAU KOTA PONTIANAK - Hartika, Widya; Farahdiba, .; Wahdina, . (Universitas Tanjungpura, 2017)
Dragonflies are spread throughout the world; the number is very abundant, especially in a wide variety of habitats. This study aims to determine the type of dragonfly in the area of ​​Sylva UNTAN Arboretum Forest City, Forest City Hall of Governors, the football field UNTAN Jogging Track and Field UNTAN as part of a green open space in the city of Pontianak. The second objective was to determine the existence of the diversity of the types of dragonflies in the area of ​​green open space, as well as to determine the species diversity index, the percentage of relative abundance, evenness index and species richness index. The study was conducted in April-May 2016, with the methods time search. Results of the study found 12 species of dragonflies. 8 species belonging to the suborder Anisoptera Libellulidae families and 4 types belong to the suborder Zygoptera which includes family Coenagrionidae and Platycnemididae. Keywords: Dragonfly, Green open space, Insect, Pontianak City